Optimasi Formula dan Karakteristik Fisik Sediaan Krim Ekstrak Daun Pegagan dengan Kombinasi Asam Stearat dan Tretanolamin - Ika Buana Januarti; Ludfi Munadhiroh; Aries Badrus Sholeh (Sultan Agung Islamic University, 2026)
Background: Gotu kola leaves contain asiaticoside which has antioxidant properties that help skin collagen production, lighten cellulite, minimize wrinkles, and remove dark spots. Cream making requires the addition of emulsifiers or emulsifying masses, because they can affect the quality and stability of the cream product, for example triethanolamine and stearic acid. In this study, we will formulate gotu kola leaf extract in a cream preparation using stearic acid and triethanolamine emulsifiers which are expected to help stability and improve the texture of the cream to be softer. The purpose of this study was to find the optimum formula for gotu kola leaf extract cream with varying concentrations of stearic acid and triethanolamine, and to test the physical characteristics of the cream preparation. Methods: The cream making method used the emulsification method. The formula optimization method used Simplex Lattice Design with physical characteristics of pH, viscosity, adhesiveness, and spreadability. Statistical analysis used a one-sample t-test to compare experimental data with predicted data. Results: The optimum formula obtained from a combination of 3.5% TEA and 5.23% stearic acid has physical properties in accordance with the requirements of cream preparations, namely homogeneous, the cream has a milky white color, odorless, soft texture, pH 5.56, spreadability 5.8 cm, adhesive power 11.15 seconds and viscosity 11833 cps. Conclusion: In the F test, a p value> 0.05 was produced, meaning that there was no significant difference between the experimental results and the predicted results.